2009
DOI: 10.2478/fhort-2013-0134
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of Pythium oligandrum and chitosan in control of Phytophthora infestans (Mont.) de Bary on potato plants

Abstract: The studies were carried out both in in vitro and in vivo conditions. The field experiment was conducted during the years 2005-2007 at the Experimental Station in Mydlniki, owned by the Department of Plant Protection at the University of Agriculture in Krakow. The aim of these studies was to determine the effect of tuber dressing and plant spraying with Polyversum (B.A.S. Pythium oligandrum) and Biochikol 020 PC (B.A.S. chitosan) bio-preparations on the top leaves and tubers of ‘Ibis’ potatoes infested by Phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Presowing treatment of pea seeds protected older plants against infection by Fusarium culmorum, F. oxysporum, Alternaria alternata, Boeremia exigua, Haematonectria haematococca, Gibberella avenacea, Peyronellaea pinodes and Thanatephorus cucumeris [9]. Chitosan was also used to dress the bulbs of ornamental plants [116] and in the protection of potato tubers against late blight and soft rot [117,118].…”
Section: Discussionmentioning
confidence: 99%
“…Presowing treatment of pea seeds protected older plants against infection by Fusarium culmorum, F. oxysporum, Alternaria alternata, Boeremia exigua, Haematonectria haematococca, Gibberella avenacea, Peyronellaea pinodes and Thanatephorus cucumeris [9]. Chitosan was also used to dress the bulbs of ornamental plants [116] and in the protection of potato tubers against late blight and soft rot [117,118].…”
Section: Discussionmentioning
confidence: 99%
“…4). The low yield-protective efficiency of Pythium oligandrum in potato cultivation was also reported by Kurzawińska and Mazur (2009). However, the authors showed significantly lower infestation of leaves and tubers by P. infestans compared to the control plot after this preparation application.…”
Section: Resultsmentioning
confidence: 73%
“…As shown by the average values of the infection index, infection rates were significantly lower in protected plants than in unprotect-ed plants. Kurzawińska and Mazur (2009) demonstrated high efficacy of Polyversum used for tuber dressing and plant spraying in late blight control. The arbuscular mycorrhizal fungus (AMF -Glomus intraradices, G. mosseae reduced the populations of Erwinia carotovora, P. infestans, Verticillium dahliaae), is a dangerous pathogen of the plant family Solanacea (Bharadwaj et al 2008).…”
Section: Resultsmentioning
confidence: 99%